Contribution of income to self‐management and health outcomes in pediatric type 1 diabetes. Issue 2 (29th December 2014) - Rechenberg, Kaitlyn; Whittemore, Robin; Grey, Margaret; Jaser, Sarah; ,
Abstract : Low income has been established as a risk factor for poorer outcomes in youth with type 1 diabetes; however, the effect of moderate income has not been studied. The purpose of this secondary analysis of baseline data from a multi‐site study was to compare glycemic control, self‐management, and psychosocial outcomes [depression, stress, and quality of life (QOL)] at different income levels in adolescents with type 1 diabetes. Youth (n = 320, mean age = 12.3 + 1.1, 55% female, 64% white, mean A1C = 8.3 ± 1.4) completed established self‐management and psychosocial measures. A1C levels were collected from medical records. Caregivers reported annual family income, categorized as high (>$80K), moderate ($40–80K), or low (<$40K). Youth from high‐income families had significantly lower A1C (mean = 7.9 ± 1.2) than those from the moderate‐income group (8.6 ± 1.7, p < 0.001) or the low‐income group (mean A1C = 8.6 ± 1.5, p = 0.003). Youth from the high‐income group reported significantly better diabetes problem solving and more self‐management goals than those from the moderate‐ or low‐income groups (both p < 0.01). Youth from the high‐income group also reported significantly fewer symptoms of depression, lower levels of perceived stress, and better QOL than those in the moderate or low‐income groups (all p < 0.05). Multivariate linear regression models were used to test psychological and behavioral predictors of A1C and QOL. Parents' education status (p < 0.05) and self‐management activities (p < 0.01) were significant predictors of hemoglobin A1c, while income (p < 0.01) and self‐management activities (p < 0.05) were significant predictors of QOL.